Predictors of Natural Disaster Preparedness Among Healthcare Providers - Ramdani Ramdani; Yanny Trisyani; Etika Emaliyawati (STIKep PPNI Jawa Barat, 2023)
Aims: Preparedness of medical personnel in dealing with disasters is strongly influenced by several factors, one of which is knowledge, attitude, role and organization in disaster management. Nowadays, healthcare profesional is facing frequent natural disaster, thus identification on their disaster preparedness is imperative. To identify factors related to the preparedness of medical personnel in handling natural disasters at the Regional General Hospital dr. Slamet, Garut Regency, West Java. Methods: This type of research was a cross-sectional study using an online survey. The sample technique used is convenience sampling with a total number of research subjects as many as 245 nurses and 54 doctors with a total of 299 respondents. The multivariate test uses simple linear regression. Results: The mean score of disaster preparedness among nurse was 137.33 (SD=16.79) and doctor was 136.07 (SD=17.40), dengan p-value 0.799. There was a significant relationship between preparedness and knowledge (r = 0.658, p-value = 0.000), attitude (r = 0.602, p-value = 0.0000), role (r = 0.541, p-value = 0.000), and organization (r = 0.610, p-value 0.000). Knowledge (B = 1.40 (95% CI = 0.62 - 2.19, p-value = 0.00), role (B = 0.94 (95% CI = 0.50 - 1.38, p-value = 0.001), and organization (B = 1.01 (95% CI = - 0.1 - 2.13, p-value = 0.035) had a significant relationship with the preparedness of medical personnel for natural disaster management with a R2 value of 0.58. Knowledge, roles, and organization were the dominant factors that significantly correlate with the preparedness of medical personnel for natural disaster management. Conclusion: Medical personnel at General Public Hospital Dr. Slamet Garut have good preparedness for natural disasters. They have good knowledge about disaster management but lack detailed planning. Attitudes towards disaster management are good, but improvement is lacking. The role of medical personnel is good, but leadership is lacking. Organizational factors, planning, policy, and professional development are significant factors affecting preparedness.